The effect of aerobic exercise and aqueous garlic extract on markers of cardiac mitochondrial biogenesis in diabetic rats - Masoumeh Ebrahimpour; Saqqa Farajtabar Behrestaq (مجله علوم پزشکی فیض (پیوسته), 2024)
Background and Aim: Exercise induces various adaptations, including increased antioxidant capacity, enhanced mitochondrial size, and improved insulin signaling. The present study aimed to investigate the effects of aerobic exercise along with aqueous garlic extract consumption on markers of cardiac mitochondrial biogenesis in diabetic rats. Methods: In this experimental study, 40 male Wistar rats (5 weeks old, weighing 162.1 ± 15.2 grams) were obtained from the Pasteur Institute. Eight rats were assigned to the healthy control group (CN). The remaining 32 rats were rendered diabetic through a single intraperitoneal injection of streptozotocin (60 mg/kg) and were randomly divided into four groups: diabetes (DM), diabetes + exercise (TDM), diabetes + garlic (GDM), and diabetes + exercise + garlic (TGDM). The exercise groups underwent an aerobic exercise program on a treadmill for 8 weeks. Additionally, each rat received 1 milliliter of garlic extract (0.4 g per 100 g of body weight) via gavage daily. Changes in the expression of PGC-1α and Nrf2 genes were measured in heart tissue using real-time PCR. Results: Induction of diabetes resulted in a significant decrease in PGC-1α (P=0.0001) and Nrf2 (P=0.0001) gene expression compared to the control group. In the TDM group, PGC-1α and Nrf2 expressions significantly increased (P=0.038 and P=0.031, respectively), as did those in the GDM group (P=0.036 and P=0.025, respectively) compared to the DM group. However, the combined intervention of exercise and garlic supplementation did not yield significant improvements compared to each intervention alone regarding PGC-1α and Nrf2 expression (P< 0.05). Conclusion: Both garlic supplementation and exercise may inhibit streptozotocin-induced cardiac damage by upregulating the PGC-1α and Nrf2 pathways. Further studies are warranted to explore this area more comprehensively.